A comparison of in-sample forecasting methods - Bischofberger, Stephan M.; Mammen, Enno (Computational statistics & data analysis, 2019)
In-sample forecasting is a recent continuous modification of well-known forecasting methods based on aggregated data. These aggregated methods are kno…
Available online 1 March 2019
Gesehen am 04.07.2019